Pemikiran Imām al-Shāfi’i tentang Talak Tafwi̅ḍ dan Relevansinya dengan Teori Kesetaraan Gender dalam Praktik Pengembangan Hukum Keluarga Islam di Indonesia - Alis Maulana; Luthfi Hadi Aminuddin (Journal of Economics, Law, and Humanities, 2022)
This thesis is the result of a literature study entitled “Imām al-Shāfi’i Thoughts on Talak Tafwi̅ḍ and Its Relevance to the Theory of Gender Equality in The Practice of Developing Islamic Family Law in Indonesia”. Academic problems are felt by the author so do this research, because there are still many people who consider that the absolute right of divorce belongs to a husband. This study aims to answer the question of what is the opinion and legal basis of Imām al-Shāfi’i thinking about the ability of the practice of divorce tafwi̅ḍ?. And how is the relevance of talak tafwi̅ḍ with the theory of gender equality in the practice of developing Islamic Family Law in Indonesia?. The results of the study concluded, Imām al-Shāfi’i argued that divorce tafwi̅ḍ the law is permissible, because of the surrender of the authority of divorce to his wife was once done by Rasullah saw. which is based on naṣ al-Qur'an surah al-Aḥzāb verses 28-29, and hadith ṣahih narration muttafaq ‘alaih from Aishah r.a. The relevance of tafwi̅ḍ divorce with the theory of gender equality, that with the practice of divorce tafwi̅ḍ this can help to lift the status/gender of women, especially in relation to divorce. When a husband submits his right to divorce authority to his wife, then surely a husband has raised his wife degree in the concept of gender equality.